Strategi Penggunaan Teknologi Informasi Dalam Meningkatkan Kualitas Pelayanan Administrasi Di MTsN 2 Aceh Barat - Agustina, Agustina; Herman, Herman; Hardianty, Sri (Seutia Hukamaa Cendekia, 2024)
One of the responsibilities in managing educational units is the use of information technology. This study aims to determine the strategy for using information technology in MTsN 2 West Aceh. This research is field research (field research, with a qualitative approach. Data collection techniques are carried out through observation, interviews, and document studies. Data processing techniques are carried out by data reduction, data presentation (data display), and data verification (conclusion drawing). The results showed that: 1) strategies for providing information technology by budgeting funds and procuring information technology software and hardware, 2) strategies for training and controlling school apparatus by guiding, fostering and involving madrasah apparatus to attend training, seminars and webinars to develop competence in the use of information technology, 3) information technology asset management strategies by maintaining and take care so that it is not easily damaged, and inventory information technology assets into the State Property (BMN) report.